Photophysical Details and O2-Sensing Analysis of a Eu(III) Complex in Polymer Composite Nanofibers Prepared by Electrospinning - Cui, Chunguo; Song, Lina; Li, Chao; Lin, Tiantian; Shi, Kaiyao (Frontiers in Chemistry, 2022)
An as-synthesized Eu(III) complex, denoted as Eu(N-DPNQ)(TTD)3, was prepared and characterized, and the antenna mechanism between these ligands and central metal emitter was studied. Here DPNQ means 10-ethyl-10H-indolo [2′,3':5,6]pyrazino[2,3-f][1,10]phenanthroline and TTD is 4,4,4-trifluoro-1-(thiophen-2-yl)butane-1,3-dione. We find that Eu(N-DPNQ)(TTD)3 emission intensity dependents on oxygen concentration, and O2-sensing skill of Eu(N-DPNQ)(TTD)3 in polymer composite nanofibers of poly (vinylpyrrolidone) (PVP) prepared by electrospinning is investigated. Results reveal that the emission quenching of Eu(N-DPNQ)(TTD)3 is caused by the ground state (triplet) oxygen quenching on antenna ligands triplet state. The Eu(N-DPNQ)(TTD)3 doped composite nanofiber with a loading level of 6 wt% exhibits the best result with sensitivity of 2.43 and response time of 10 s, along with linear response.